2022
DOI: 10.1039/d1fd00096a
|View full text |Cite
|
Sign up to set email alerts
|

Manipulation of amorphous precursors to enhance zeolite nucleation

Abstract: Crystallization in media comprised of amorphous precursors is becoming a more common phenomenon for numerous synthetic, biological, and natural materials that grow by a combination of classical and nonclassical pathways....

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 71 publications
0
12
0
Order By: Relevance
“…272 The adsorption of polymers such as polydiallyldimethylammonium (PDDA) 273 or polyacrylamide 274 on zeolite precursors can also induce particle aggregation at an optimal polymer concentration (Figure 13d), enhancing the rate of zeolite crystallization. 275 It was hypothesized that the interstitial regions between aggregated precursor particles provide a confined region that promotes zeolite nucleation through a more rapid exchange of species between solid and solution phases, as illustrated in Figure 13d. The presence of aluminum on the external surfaces of colloidal particles can affect the rate of silica dissolution, which is often inferred from changes in solution pH or conductivity.…”
Section: Colloidal Particlesmentioning
confidence: 99%
“…272 The adsorption of polymers such as polydiallyldimethylammonium (PDDA) 273 or polyacrylamide 274 on zeolite precursors can also induce particle aggregation at an optimal polymer concentration (Figure 13d), enhancing the rate of zeolite crystallization. 275 It was hypothesized that the interstitial regions between aggregated precursor particles provide a confined region that promotes zeolite nucleation through a more rapid exchange of species between solid and solution phases, as illustrated in Figure 13d. The presence of aluminum on the external surfaces of colloidal particles can affect the rate of silica dissolution, which is often inferred from changes in solution pH or conductivity.…”
Section: Colloidal Particlesmentioning
confidence: 99%
“…Rimer and co-workers showed that alkali (K + or Na + )-infused amorphous precursors reduced the crystallization time by more than 50% for LTL-, MOR-, and CHA-type zeolites compared to synthesis using asreceived fumed silica, whereas there was little impact on the synthesis of MFI-type zeolite. 105,129,130 Although the exact effect of alkali-infused amorphous silica on enhancing the rates of crystal formation remains elusive, they explained the presence of alkali metal inside the amorphous silicates could act as an inorganic SDA and promote particle aggregation.…”
Section: Perspectives and Outlookmentioning
confidence: 99%
“…Recent studies have shown the versatility and effectiveness of adjusting the nucleation/crystallization growth kinetics of zeolites to form an optimal morphology. [14,[39][40][41][42][43] Notably, seeded methods can provide nuclei or growth sites directly into the nutrients, which can increase crystallization rates and reduce crystal size or introduce mesopores. [40,[44][45][46][47] Although these methods are effective, the produced hierarchical zeolites are usually polycrystalline aggregates of small particles or with sole isolated mesopores.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, developing effective ways to modulate the growth/crystallization behavior of zeolites to create intrapenetrated hierarchical structure is highly desired to eliminate the need of expensive templates and avoid the fragile framework caused by removing organic mesoporogens. Recent studies have shown the versatility and effectiveness of adjusting the nucleation/crystallization growth kinetics of zeolites to form an optimal morphology [14,39–43] . Notably, seeded methods can provide nuclei or growth sites directly into the nutrients, which can increase crystallization rates and reduce crystal size or introduce mesopores [40,44–47] .…”
Section: Introductionmentioning
confidence: 99%